Simulation comparison of SSE and TDOA methods for UHF direction finding of partial discharge in substation area. (December 2020) - Zhang, Fei; Wei, Bin; Liang, Bo; Wang, Hong; Wang, Baole; Feng, Guobin
Abstract: Partial discharge (PD) is not only the main cause of insulation fault for power equipment, but also an important sign of insulation defects. Using the PD detection system based on ultra-high frequency (UHF) antenna array, the PD localization can be realized in air-insulation substation. At present, the methods commonly used in PD detection system localization include time difference of arrival (TDOA) method and spatial spectrum estimation (SSE) method. This paper introduced the principles of these two methods, and proposed a simulation system for PD direction finding. Using this system, the direction finding performance of the TDOA method and the SSE method under different signal-to-noise ratio, incident azimuth angle, rising edge time and array element spacing are compared. The conclusion shows that when the SNR is less than 0 dB or the element spacing is less than 0.23 m, the SSE system has better direction finding performance. When the element spacing is greater than 0.23 m, the SSE system will be fuzzy in direction finding. At this time, the TDOA algorithm can achieve higher direction finding accuracy.